Some Methods of Describing Echolocation Calls of Bats Using Cohen’S Class and Wavelet Algorithms - HERMAN, Krzysztof (Archives of Acoustics, 2008)
In this paper some digital signal processing algorithms, that are used for describing bats’ echolocation calls of two different species of bats (Myotis daubentoni, Nyctulus noctula) are presented. Analyzed algorithms are dedicated to calculate time frequency (TF) representation of digital signals. Spectrogram of the bat sonar call gives us information about many important features of the signal like type of frequency modulation which is one of the most important signal parameter. Comparative analysis of the algorithms mentioned in this paper suggests that we can select the best suitable method of analysis of bat’s sonar signals.